2013
DOI: 10.3892/or.2013.2900
|View full text |Cite
|
Sign up to set email alerts
|

Relapse-associated microRNA in gastric cancer patients after S-1 adjuvant chemotherapy

Abstract: S-1 has been recommended as adjuvant chemotherapy in patients after curative surgery for gastric cancer. However, some patients suffer recurrence even after S-1 adjuvant chemotherapy. The present study was conducted to find a predictive marker of the efficacy of S-1 adjuvant chemotherapy. We examined the microRNA (miRNA) expression of 35 patients who underwent S-1 adjuvant chemotherapy after curative surgery (R0) for pathological stage II or III gastric cancer. miRNAs were extracted from formalin-fixed, paraff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 24 publications
2
23
0
1
Order By: Relevance
“…Its downregulation in tumoral versus normal tissue has been reported in osteosarcoma [21], in colorectal cancer [13, 22], hepatocarcinoma [14] and gastric tumors [23]. A low expression of miR-422a is a marker of poor prognosis in osteosarcoma [21] and colorectal cancer [24] and of poor RFS in hepatocarcinoma [25].…”
Section: Discussionmentioning
confidence: 99%
“…Its downregulation in tumoral versus normal tissue has been reported in osteosarcoma [21], in colorectal cancer [13, 22], hepatocarcinoma [14] and gastric tumors [23]. A low expression of miR-422a is a marker of poor prognosis in osteosarcoma [21] and colorectal cancer [24] and of poor RFS in hepatocarcinoma [25].…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have revealed the involvement of miR-422a in human cancers. It is dysregulated in osteosarcoma [19], colorectal cancer [2022], hepatocarcinoma [23], and gastric cancer [24]. miR-422a is an indicative marker for poor prognosis in osteosarcoma, gastric cancer, and hepatocarcinoma [23].…”
Section: Discussionmentioning
confidence: 99%
“…Pouladi et al (59) predicted a binding site for miR-4732-5p in the 5′ UTR of telomerase cajal body protein 1 mRNA. In addition, miR-4732-5p has been revealed to be closely associated with recurrence in gastric cancer patients treated with S-1 adjuvant chemotherapy (60). Importantly, the TF-mRNA regulatory network constructed in the present study revealed that the target genes of the miRNAs investigated were potentially regulated by numerous transcription factors, which highlights the critical roles of these miRNAs and their targets in physiological and pathological processes.…”
Section: Discussionmentioning
confidence: 99%